2008
DOI: 10.1073/pnas.0803214105
|View full text |Cite
|
Sign up to set email alerts
|

The mammary microenvironment alters the differentiation repertoire of neural stem cells

Abstract: transplantation ͉ niche ͉ plasticity ͉ trans-differentiation ͉ regeneration S omatic stem cells are defined by how they function physiologically in the presence of heterologous cells, that is, the microenvironment or stem cell niche that balances protecting stem cells from exhaustion and protecting the host from unregulated stem cell growth. The dominance of the niche over the stem cell's autonomous phenotype has been demonstrated in several reports involving cells crossing lineage ''boundaries'' to regenerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 15 publications
3
123
2
3
Order By: Relevance
“…Androgen receptor and Nkx3.1 are two of the earliest markers of prostatic differentiation that are expressed at low/undetectable levels in mammary gland epithelium. Foxa1 interacts with AR and multiple prostatic enhancers to control androgen-induced activation of both human and rodent prostate-specific genes [18]. Foxa1 binding is also essential for ER--chromatin interactions and subsequent expression of estrogen target genes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Androgen receptor and Nkx3.1 are two of the earliest markers of prostatic differentiation that are expressed at low/undetectable levels in mammary gland epithelium. Foxa1 interacts with AR and multiple prostatic enhancers to control androgen-induced activation of both human and rodent prostate-specific genes [18]. Foxa1 binding is also essential for ER--chromatin interactions and subsequent expression of estrogen target genes [27].…”
Section: Discussionmentioning
confidence: 99%
“…1B). A recent study demonstrated that neural stem cells transdifferentiated into mammary epithelial cells when they were transplanted into adult mammary mesenchyme (37). Therefore, the questions of whether the epithelial fate determination is reversible or irreversible and whether once-determined cilial cells can transdifferentiate into secretory cells were addressed.…”
Section: Fate Determination Of Epithelial Cells By Mesenchymal Cell Lmentioning
confidence: 99%
“…The importance of mesenchyme, as the embryonic niche, in determining organ identity and fate of the epithelium was demonstrated long ago by classic embryological studies (2,3). More recent studies have shown, however, that postnatal stroma, a derivative of embryonic mesenchyme, is essential for maintenance of cell fate and differentiation status in adult life (4,5). Indeed, abnormal stroma can lead to the formation of a cancer microenvironment, and it plays a causative role during tumor onset and progression (1,6).…”
mentioning
confidence: 99%